Sectarian tensions, islamophobia, and decolonization: comparing Jasser Auda’s and Jonathan Brown’s analysis of the hadiths concerning Aisha’s marital age - Muzakkir, Muhamad Rofiq; Muwahidah, Siti Sarah; Utsany, Royan; Rohmansyah, Rohmansyah (Indonesian Journal of Islam and Muslim Societies, 2023)
The ongoing debate surrounding the hadiths on Aisha’s age of marriage has givenrise to two main positions among Muslim scholars, namely: the rejectors, thosewho reject the hadiths’ validity and propose the view that Aisha got married atan older age, and the defenders, those who defend them as valid hadiths andaccept that Aisha consummated her marriage at the early age of nine years old. Inthis study, we examine this issue through the opposing arguments offered by twocontemporary Muslim scholars: Jasser Auda, who represents the view of hadithrejectors, and Jonathan Brown, who represents those who accept the validity of thehadiths. These two scholars have been chosen to represent these two standpointsmainly because of their novel and distinctive theoretical contributions to theongoing debate. Entangled in this debate is the issue of whether pre-modernreality can be assessed by using modern norms. We employ critical analysis onthe epistemological and methodological aspects surrounding the two scholars’interpretations of the hadiths of Aisha’s age of marriage. We argue that threesignificant features distinguish Auda and Brown’s dispositions. These are: first,their different conceptions of the interplay between politics, knowledge, andmemory; second, their differing epistemological approaches to hadith science;and third, their opposing assumptions about the universality of modern norms.